PENGARUH GAYA MANAJEMEN DAN STRUKTUR ORGANISASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI - Buana Handoko, Rangga Restu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine how much influence the management style and structure organization on the quality of accounting information system in the Islamic sharia BJB and BJB in Bandung. The research approach used in this study is descriptive and verification analysis using primary data. The sampling technique used was with purposive sampling. The Statistical analysis used in this study is a classic assumption test, validity test, reliability test, and multiple linear regression analysis. Number of population and sample of this study 35 respondents, sampling using purposive samping method with sources obtained through the result of filling out the questionnaire and processed with the help of SPSS software Version 25.0. This results showed that the influence of management style and organization structure affect the quality of accounting information system both partially and simultaneously. Partially management style influences the quality of accounting information system and organization structure influences the quality of accounting information system. Simultaneously management style and organization structure significant affect the quality of accounting information system.